Contextualizing the impact of prenatal alcohol and tobacco exposure on neurodevelopment in a South African birth cohort: an analysis from the socioecological perspective - Xia, Yingjing; Rebello, Vida; Bodison, Stefanie C.; Jonker, Deborah; Steigelmann, Babette; Donald, Kirsten A.; Charles, Weslin; Stein, Dan J.; Ipser, Jonathan; Ahmadi, Hedyeh; Kan, Eric; Sowell, Elizabeth R.; et al. (Frontiers in Integrative Neuroscience, 2023)
Background Alcohol and tobacco are known teratogens. Historically, more severe prenatal alcohol exposure (PAE) and prenatal tobacco exposure (PTE) have been examined as the principal predictor of neurodevelopmental alterations, with little incorporation of lower doses or ecological contextual factors that can also impact neurodevelopment, such as socioeconomic resources (SER) or adverse childhood experiences (ACEs). Here, a novel analytical approach informed by a socio-ecological perspective was used to examine the associations between SER, PAE and/or PTE, and ACEs, and their effects on neurodevelopment. Methods N = 313 mother-child dyads were recruited from a prospective birth cohort with maternal report of PAE and PTE, and cross-sectional structural brain neuroimaging of child acquired via 3T scanner at ages 8–11 years. In utero SER was measured by maternal education, household income, and home utility availability. The child’s ACEs were measured by self-report assisted by the researcher. PAE was grouped into early exposure (<12 weeks), continued exposure (>=12 weeks), and no exposure controls. PTE was grouped into exposed and non-exposed controls. Results Greater access to SER during pregnancy was associated with fewer ACEs (maternal education: β = −0.293,p = 0.01; phone access: β = −0.968,p = 0.05). PTE partially mediated the association between SER and ACEs, where greater SER reduced the likelihood of PTE, which was positively associated with ACEs (β = 1.110,p = 0.01). SER was associated with alterations in superior frontal (β = −1336.036, q = 0.046), lateral orbitofrontal (β = −513.865, q = 0.046), caudal anterior cingulate volumes (β = −222.982, q = 0.046), with access to phone negatively associated with all three brain volumes. Access to water was positively associated with superior frontal volume (β=1569.527, q = 0.013). PTE was associated with smaller volumes of lateral orbitofrontal (β = −331.000, q = 0.033) and nucleus accumbens regions (β = −34.800, q = 0.033). Conclusion Research on neurodevelopment following community-levels of PAE and PTE should more regularly consider the ecological context to accelerate understanding of teratogenic outcomes. Further research is needed to replicate this novel conceptual approach with varying PAE and PTE patterns, to disentangle the interplay between dose, community-level and individual-level risk factors on neurodevelopment.